Signed 2-independence of Cartesian product of directed cycles and paths - Wang, Haichao,; Kim, Hye Kyung, (Utilitas Mathematica, 2013)
A two-valued function f: V(D) → {-1,1} defined on the vertices of a digraph D =(V(D),A(D)) is called a signed 2-independence function if f(N∼[v]) ≤ 1 for every v in D. The weight of a signed 2-independence function is f(V(D)) = Σv∈v(D)f(v). The maximum weight of a signed 2-independence function of D is the signed 2-independence number α2s(D) of D. Let Cm × Pn be the Cartesian product of directed cycle Cm and directed path Pn. In this paper,we determine the exact values of α2s(Cm × Pn) when 2 ≤ m ≤ 5 and n≥ 1.